Affective commitment, home-based working and the blurring of work–home boundaries: Evidence from Germany - Yvonne Lott; Anja-Kristin Abendroth (New Technology, Work and Employment, 2022)
Analysis of data from the representative German Linked Personnel Panel revealed that, overall, the use of home-based working is associated with a higher affective organisational commitment on the part of employees. However, this is less often the case when the use of home-based working involves the blurring of work–home boundaries. Perceived trust and fairness on the part of supervisors mediates the association between employees' experiences with working from home and their affective commitment. These results show that experiences with home-based working shape employees' perceptions of trust and fairness in their exchange relations with supervisors and thus their affective commitment to the organisation. Employees' experiences with home-based working that reflect its supportive implementation by their employers and supervisors are critical for their commitment. Our results provide the first evidence that in exchange relations between employees and supervisors, perceived fairness is as important as perceived trust.
Keywords: 330; affective organisational commitment; blurred boundaries; employee–supervisor relations; experiences with home-based working; fairness; home-based working; social exchange; trust; work–life balance